Analysis of Use of Welded Angle and Drop Hollow as Reusable Temporary Supporting in Metal deck Slabs Viewed From Performance of Costs And Time - Fertilia, Novika Candra; Swasti, Sani Sona (Journal of World Conference (JWC), 2020)
Like the project in general, slab work on Project Indonesia 1 uses one material, namely metal deck. The upper structure slab consists of 64 floors with a majority of 90% using a metal deck system. Where these components require support that can carry the workload, rebar, and fresh concrete. Starting with Metaldeck's non-reusable / fixed supporting (angle & anchor) design which is quite difficult to apply in the field, it has an impact on increasing time and increasing the cost of work. So the engineering team has the innovation of replacing non-reusable / fixed supporting material (angle & anchor) with reusable material (angle & drop hollow). Cost analysis is sought by calculating the RAB (Cost Budget Plan) using the unit price analysis used by the DKI Jakarta Government and how efficient the time gained. Based on the results of calculations and interviews with relevant experts on the project, the implementation of temporary supporting work costs was carried out using a non-reusable method of Rp.3,211,000,000.00. As for the implementation of the reusable method of Rp.649,916,800. There is a difference in cost between the non-reusable and reusable methods of Rp. 2,561,083,200.00. Where to implement the temporary supporting reusable method is cheaper than using the non-reusable initial method. Then in terms of installation time, the temporary supporting using the non-reusable method was 520 days while for the reusable method it was 260 days. There is a difference between the non-reusable and 260-day reusable methods. The results obtained that the use of Welded Angle & Drop Hollow as Temporary Supporting is more effective and efficient than using the initial Non-reusable method.